If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2w + 5)(2w + -5) = 0 Reorder the terms: (5 + 2w)(2w + -5) = 0 Reorder the terms: (5 + 2w)(-5 + 2w) = 0 Multiply (5 + 2w) * (-5 + 2w) (5(-5 + 2w) + 2w * (-5 + 2w)) = 0 ((-5 * 5 + 2w * 5) + 2w * (-5 + 2w)) = 0 ((-25 + 10w) + 2w * (-5 + 2w)) = 0 (-25 + 10w + (-5 * 2w + 2w * 2w)) = 0 (-25 + 10w + (-10w + 4w2)) = 0 Combine like terms: 10w + -10w = 0 (-25 + 0 + 4w2) = 0 (-25 + 4w2) = 0 Solving -25 + 4w2 = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 4w2 = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 4w2 = 0 + 25 4w2 = 0 + 25 Combine like terms: 0 + 25 = 25 4w2 = 25 Divide each side by '4'. w2 = 6.25 Simplifying w2 = 6.25 Take the square root of each side: w = {-2.5, 2.5}
| (9x+4y)(9x+-4y)=0 | | -4/3=2r | | log(80x+60)=2+log(x-3) | | 60=-4/5k | | 5/8x-6/7=4/3-x | | 3x^3+40x^2-60=0 | | -h+3=-2b | | 5a^2b-10ab+8a-8= | | 7x+6xy-3x^2+8x^2-10x= | | 1/2mr=f | | (X^2)-14x-16y-129=0 | | 3x-14=5x+6 | | f=1/2mf | | (2x-2)*(2x+6)-(3x-2)2=(2x-5)2-(2x+7)*(2x-1)-217 | | 4cosx+3=6 | | 3-8=16 | | f(x)=x+4cosx | | -3x^2+150x-288=0 | | 85=7+2x | | 12(-3)+3y=33 | | 3x-2/35/2x-4 | | 4h+5h-h-7h=7 | | 17r-r+2r-12r-5r=16 | | 7=-1/3w | | -15m+-18m-10m+10m+m=12 | | logx^4=logx^3 | | 8y-4=3x-3 | | (35v^4z^5-25v^6z^5)/(-4v^5z^2) | | y=5x^4-3x^2-7x+4 | | 8+1(-2)+7= | | .7x^2=4.2x+0.7 | | y=5x^2-3x^2-7x+4 |